TRANSFUSION OF RED BLOOD CELLS IN PATIENTS WITH A PRE-HOSPITAL GCS ≤ 8 AND NO EVIDENCE OF SHOCK IS ASSOCIATED WITH WORSE OUTCOMES - Elterman, Joel (2013)
BACKGROUND: Red blood cell transfusion practices vary and the optimal hemoglobin for patients with traumatic brain injury (TBI) has not been established. We sought to identify the interaction between initial hemoglobin (Hgb) and red cell transfusion on 28-day survival, Acute Respiratory Distress Syndrome (ARDS) free survival, Multi-organ dysfunction (MODs) score, and 6-month Glascow Outcome Score extended (GOSE) score in a cohort of patients with a pre-hospital Glascow Coma Score (GCS) less than or equal to 8 and no evidence of shock. METHODS: A retrospective review of data collected prospectively as part of a randomized, controlled trial involving emergency medical services (EMS) agencies within the Resuscitation Outcomes Consortium was conducted. In patients with a GCS ≤ 8 without evidence of shock {defined by a systolic blood pressure (SBP) <70 or SBP of 70–90 with a heart rate (HR) ≥ 108}, the association of red cell transfusion with 28-day survival, ARDS free survival, MODs score and 6 month GOSE was modeled using multivariable logistic regression with robust standard errors adjusting for age, sex, injury severity (ISS), initial GCS, initial SBP, highest field HR, penetrating injury, fluid use, study site and Hgb. RESULTS: 1158 patients had a mean (m) age of 40, 76% were male and 98% suffered blunt trauma. The initial GCS (m) was 5 and initial SBP (m) was 134. The head abbreviated injury score (AIS) (m) was 3.5. A categorical interaction of red cell transfusion stratified by initial Hgb showed when the first hemoglobin was >10 grams/deciliter (g/dL), volume of pRBC was associated with a decreased 28 day survival (odd ratio [OR] 0.83 per unit with a 95% confidence interval [CI] of [0.74, 0.93] p<0.01) and decreased ARDS free survival (OR 0.82 per unit (95% CI [0.74, 0.92] p<0.01). When the initial Hgb was > 10, each unit of blood transfused increased the MODs score by 0.45 (Co-efficient 95% CI [0.19, 0.70] p-value<0.01). CONCLUSION: In patients with a suspected TBI and no evidence of shock, transfusion of red blood cells was associated with worse outcomes when the initial hemoglobin was > 10. There was no relationship between blood transfusion and outcomes in the patients with initial hemoglobin ≤ 10. LEVEL OF EVIDENCE: II